Higher yield in duodenoscope cultures collected with addition of neutralizing agent. (February 2023) - Kwakman, J.A.; Vos, M.C.; Bruno, M.J.
Summary: Aim: Microbiological cultures are the gold standard in the monitoring of duodenoscope reprocessing. However, many different sampling and culturing techniques are used, making it difficult to compare results. The latest Centers for Disease Control and Prevention protocol advises the use of a neutralizer to deactivate any remaining disinfectants in the samples. This study compared culturing results of duodenoscope samples collected with and without addition of a neutralizer. Methods: Six duodenoscopes were soiled with gut bacteria in a non-clinical experimental setting and reprocessed afterwards. Samples of the tip and working channel were collected immediately after decontamination or after drying. Dey-Engley (DE) broth was added as a neutralizer to the samples of four duodenoscopes; samples for the other two duodenoscopes were collected without the addition of DE broth. Results: Post-decontamination cultures were significantly more likely to be positive for growth of the applied micro-organisms in the group of samples with DE broth (88.1% vs 20.2%; P <0.0001). Post-drying samples were significantly more likely to be positive in the group of samples without DE broth (75.7% vs 33.4%; P <0.001). Conclusion: The addition of DE broth to samples collected from wet duodenoscopes increases the yield of those cultures. Remaining disinfectants in wet duodenoscopes can lead to false-negative results. This can be overcome by adding a neutralizer, such as DE broth, to the samples. The higher yield after drying in the group without neutralizer could be due to biofilm formation in these two duodenoscopes, but this was not investigated. Standardization of the sampling method can help to compare both clinical and study results regarding duodenoscope contamination.